Enjoying the golden years: social participation and life satisfaction among Chinese older adults - Wu, Min; Yang, Dan; Tian, Yihao (Frontiers in Public Health, 2024)
Introduction Older adults commonly face the risk of social isolation, which poses a significant threat to their quality of life. This study explores the association between social participation and life satisfaction among older Chinese adults. Methods Data were sourced from the 2018 China Health and Retirement Longitudinal Study. Regression analysis and mediation analysis were employed to examine the relationship between social participation and life satisfaction, with a focus on the roles of loneliness and self-rated health. Results The results indicate that social participation is significantly positively associated with older adults' life satisfaction. Furthermore, the positive association is more pronounced with increased diversity in social activities. Mediation analysis reveals that reductions in feelings of loneliness and improvements in health levels mediate the relationship between social participation and life satisfaction. Further analysis showed that social participation had a greater positive association among rural older adults and those lacking family companionship. Discussion This study provides evidence for enhancing life satisfaction among older adults and highlights the importance of diversity in social participation.